Total Synthesis, Mechanism of Action, and Antitumor Efficacy of Camptothecin and Some of its Analogues - Bacherikov, Valeriy A. (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Over the past 55 years of research, various experimental methods have been developed for the total synthesis of the anticancer camptothecin, a potent antitumor antibiotic, and its numerous active derivatives. The discoveries made in synthetic pathways of the camptothecin heterocyclic core have contributed significantly to the theory and strategy of directed organic synthesis aimed at finding effective anticancer drugs. The synthetic, medicinal chemistry of camptothecin, the development of structures of anticancer camptothecin analogues, and the mechanism of their activity in inhibiting the growth of different types of cancers, such as lung, ovarian, breast, pancreas, and stomach cancers are analyzed. Various structural modifications in the A, B, C, D, and E-rings of the camptothecin molecule have been thoroughly studied to improve bioavailability and diminish toxicity. Modern synthetic approaches to the camptothecin analogues and several semi-synthetic methods are reviewed.
Keywords: anticancer drugs